Risk Culture and Risk Management within Gauteng Government Departments - Marota, Madiagane Rahab (University of the Witwatersrand, Johannesburg, 2024)
Regardless of the sector, organisations are faced with various risks, and risk culture has been identified as the key barrier to effective risk management. The financial crises exposed shortcomings in risk culture, as well as insufficient risk management systems and controls, resulting in substantial losses and institutional failures. The primary purpose of the study was to evaluate whether risk culture influences the implementation of risk management within the Gauteng Provincial Departments. The study employed a quantitative and positivist research methodology. Data was gathered utilising a cross- sectional approach through questionnaire. 81 cases were collected from senior management in various departments that were chosen. Cronbach's alpha was utilised as the appropriate measure for assessing reliability. The results showed that leadership support, communication, and accountability are the primary factors influencing effective risk management, whereas risk awareness and risk behaviour did not show a meaningful correlation. A robust risk culture is essential for effective risk management within an organisation, and it should be integrated into all departmental processes
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Risk Culture; Risk Management; Leadership Support; Risk Awareness; SDG-8: Decent work and economic growth